Pemantauan Kepadatan Megabentos Target Pada Terumbu Karang di Perairan Leato Selatan Kecamatan Dumbo Raya Provinsi Gorontalo - Hanafi, Andi Muhammad Ali; Yusuf, Kamil; Hamsiah, Hamsiah (Program Studi Ilmu Kelautan Fakuktas Ilmu Perikanan dan Kelautan Universitas Muslim Indonesia, 2024)
Megabenthos target associated with coral reefs include spiny starfish, blue starfish, sea urchins, sea cucumber, clams, Drupella spp., trocha snail, and lobsters which is ecologically used as an indicator for monitoring the healt condition of coral reefs and is benefical for the community’s economy.The aim of this research is to determine the density level and distribution pattern of megabenthos target on coral reefs in the waters of South Leato, Dumbo Raya Subdistrict, Gorontalo Province. Method used in collecting megabenthos data is with Bentos Belt Transect. Observation results show that the megabenthos target found in South Leato waters were seven types consisting of sea cucumber, clams, trocha snail, spiny starfish, Drupella spp., sea urchins, and blue starfish. The megabenthos target density range values obtained are 0,007 – 0,435 ind/m2, and for morisita index values ranging 0 - 0,6655 id with the distribution pattern of the megabenthos target found all being unifom.